Effect of Carillon Mitral Contour System on patient‐reported outcomes in functional mitral regurgitation: an individual participant data meta‐analysis - Khan, Muhammad Shahzeb (ESC Heart Fail, 2021)
AIMS: The Carillon Mitral Contour System has been shown to reduce mitral regurgitation and left ventricular volumes in symptomatic heart failure patients with functional mitral regurgitation. We sought to evaluate the effects of the Carillon device on quality of life and functional capacity in these patients. METHODS AND RESULTS: An individual participant data meta‐analysis was conducted utilizing data from REDUCE‐FMR, TITAN, and TITAN II studies. The main outcomes assessed were changes from baseline in Kansas City Cardiomyopathy Questionnaire overall summary scores (KCCQ‐OSS), 6 min walk test (6MWT) distance, and New York Heart Association (NYHA) classification at Months 1 and 12 after device implantation. Subgroup analyses were conducted for patients with severe functional mitral regurgitation (Grade 3 or 4). Pooled estimates were calculated using a random‐effects model and are presented as weighted proportions or weighted mean differences along with 95% confidence intervals (CIs). Among 139 patients included in the analysis, Carillon device significantly improved the 6MWT distance (63.0 m; 95% CI 18.8–107.2, P = 0.0056) and KCCQ‐OSS score (15.1; 95% CI 5.6–24.7, P = 0.0022) at 1 month from baseline. These benefits were sustained at 12 months (64.1 m; 95% CI 13.2–115.0, P = 0.0141, for 6MWT distance, and 12.3; 95% CI 4.7–19.8, P = 0.0019, for KCCQ‐OSS score). More than 50% of the patients had improvements in KCCQ‐OSS by ≥5 (60.4%; 95% CI 47.4–72.1) and 10 points (50.5%; 95% CI 34.9–66.0) at 12 months. Almost half of the patients experienced a ≥1 class improvement in NYHA class after implantation of the device at 1 month (67.9%; 95% CI 37.3–88.3) and at 12 months (48.8%; 95% CI 31.8–66.2). Results remained similar for KCCQ‐OSS, 6MWT distance, and NYHA classification when only patients with Grade 3 or 4 mitral regurgitation were analysed. The pooled estimates of 30 day and 1 year all‐cause mortality were 2.2% (95% CI 0.7–6.5) and 17.3% (95% CI 11.8–24.5), respectively. CONCLUSIONS: The Carillon Mitral Contour System significantly improved patient‐reported quality‐of‐life outcomes in heart failure patients with functional mitral regurgitation.